A diffusion model for the titanium borides on pure titanium. (1st November 2016) - Keddam, M.; Taktak, S.; Tasgetiren, S.
Abstract : In the present study, commercial pure titanium was successfully plasma paste borided using borax paste at a temperature of 700, 750 and 800°C for 3, 5 and 7 h. The X-ray diffraction and scanning electron microscopy techniques revealed the presence of both TiB2 top-layer and TiB whiskers sub-layer. The formation rates of the TiB2 layer and TiB whiskers were found to have a parabolic character at all applied process temperatures. Based on the present Ti borides growth data, correspondent diffusion temperature and time, an analytical diffusion model was used to estimate boron diffusion coefficients and activation energies of the boride phases in a binary multiphase Ti–B system. Depending on the temperature and layer thickness, the activation energies of boron in TiB2 and TiB phases were determined to be 137.55 ± 0.5 and 55.21 ± 0.5 kJ mol −1, respectively. These values of boron activation energies for pure titanium were compared to the literature data.